Erosion - corrosion coupling analysis of shale gas production pipe. (August 2022) - Chen, Yong; Wu, Haochen; Chen, Yanjun; Li, Pengcheng; Wang, Qiliang
Highlights: In this paper, the failure mechanism of shale gas production pipe is studied by combining mechanical properties, physical and chemical analysis and numerical simulation analysis. The results of this paper provide a reference for coupled failure analysis of shale gas pipeline erosion and corrosion. Abstract: Shale gas produced from wells contains free water, solid particles, and other corrosive substances, so shale gas production lines are at high risk of failure. The bending pipe of gas production in Shunan Gas Mine failed during service. In order to find out the causes of the failure of the bends and to provide technical support for the safe transmission of shale gas, Tensile testing machine, Vickers hardness tester, Charpy notch impact testing machine and metallographic microscope were used to test the mechanical properties and metallographic structure of the pipe sample material. The corrosion by- products were analyzed by scanning electron microscope, energy dispersive spectrometer and X-ray diffractometer. Finally, the Computational Fluid Dynamics (CFD) is used to simulate the erosion behavior of the curved pipe under different working conditions. The results show that the chemical composition, tensile strength, yield strength, hardness, impact performance and grain size grading of the gas bending pipe meet the relevant requirements. The corrosion by-product was identified as FeCO3 by the microstructure characterization analysis, energy spectrum analysis and XRD. The corrosion by CO2 was the main cause for perforation and pitting pits. CFD simulation results show that sand gas has obvious erosion phenomenon on the pipe wall, and with the increase of flow rate, the erosion rate of sand and gravel on the pipe sample increases, and the larger the particle size, the higher the erosion rate of sand and gravel on pipe sample. Combined with the erosion and corrosion results, it is concluded that the erosion of sand-bearing gas makes the inner wall material of the elbow fall off, accelerates the corrosion of CO2 on the pipe wall, and finally leads to the failure of the gas production elbow.